The NR-6: a new brief measure of nature relatedness - Nisbet, Elizabeth K.; Zelenski, John M. (Frontiers in Psychology, 2013)
The construct of (dis)connection with nature or 'nature relatedness' has become increasingly useful in the study of environmental behaviour as well as psychological health and well-being. Strong nature relatedness is associated with greater happiness and ecologically sustainable behaviour. A number of scales reliably assess individual differences in nature relatedness, but some circumstances may necessitate a brief measure. We developed a short-form version of the nature relatedness scale (NR-6), comprised of 6 items from the 'self' and 'experience' dimensions, and tested the new scale's predictive ability across multiple samples and with longitudinal data in students, community members, and business people. The new NR-6 scale demonstrated good internal consistency, temporal stability, and predicted happiness, environmental concern, and nature contact. This new brief measure of connectedness may have advantages where time and space are limited and the research context requires an assessment of connectedness elements rather than environmental attitudes.